Using claw marks to study lion predation on giraffes of the Serengeti. (6th November 2012) - Strauss, M. K. L.; Packer, C.
Abstract Although lions Panthera leo are the main predators of the giraffe Giraffa camelopardalis, interactions between these species are rarely observed directly. As a consequence, little is known about the effects of lions on giraffe mortality and behavior. We test patterns of lion predation on Masai giraffes Giraffa camelopardalis tippelskirchi using a new methodology: lion claw marks observable on the skin of live giraffes. We studied 702 individually known giraffes in 3 non‐neighboring areas of Serengeti National Park, Tanzania between August 2008 and November 2010. Lion claw marks were observed on 13% of giraffes older than 1 year. Claw marks were most frequently detected on giraffe hindquarters and flanks, revealing that non‐lethal lion attacks occur most often from the rear. No claw marks were observed on calves (0–1 year), suggesting that calves rarely survive lion attacks. In the adult age class (>5 years), claw‐mark prevalence was significantly higher among females than males. We observed substantial variation in claw‐mark prevalence across study areas, indicating that lion predation risk may be heterogeneous within Serengeti. We find that claw marks are an important source of data on interactions between lions and giraffes.